Transient Stress Intensity Factors of Functionally Graded Hollow Cylinders with Internal Circumferential Cracks - Iman Eshraghi; Nasser Soltani; Mohammad Rajabi (Latin American Journal of Solids and Structures)
Abstract In this paper, transient thermomechanical stress intensity factors for functionally graded cylinders with complete internal circumferential cracks are obtained using the weight function method. The finite difference method is used to calculate the time dependent temperature distribution and thermal stresses along the cylinder thickness. Furthermore, finite element analysis is performed to determine the weight function coefficients and to investigate the accuracy of the predicted stress intensity factors from the weight functions. Variation of the stress intensity factors with time and effects of the material gradation on the results are investigated, as well. It is shown that the proposed technique can be used to accurately predict transient thermomechanical stress intensity factors for functionally graded cylinders with arbitrary material gradation.